Transitions in ICT-Integrated Teaching and Learning in Trans-disciplinary STEM Education: A Systematic Review Through a Scopus Bibliometric Analysis (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
The integration of digital technologies into teaching and learning practices accelerated significantly during the COVID-19 pandemic, driving enduring pedagogical shifts that persisted beyond the pandemic. At the onset, educational institutions faced a choice: suspend curricular delivery or embrace alternative modalities to maintain instruction. Most opted for the latter, catalysing the widespread adoption of virtual technologies. Although virtual tools predated the COVID-19 pandemic, the pandemic dramatically increased their centrality in educational practice. This research is based on a systematic review of peer-reviewed literature from 2010 to 2024. Using the Substitution, Augmentation, Modification, and Redefinition (SAMR) model, this systematic study maps current pedagogical practices and interrogates the affordances and constraints of digital tools in teaching, learning, and assessment. The findings reveal incremental movement toward transformative use, but emphasise that substitution and augmentation remain dominant. The study contends that a deeper pedagogical transformation is necessary to fully harness information and communication technology (ICT) for innovative, trans-disciplinary science, technology, engineering, and mathematics (STEM) learning environments.
Keywords: Bibliometric analysis; digital learning; STEM education; pedagogical transformation